Pentose Phosphate Pathway Regulates Tolerogenic Apoptotic Cell Clearance and Immune Tolerance - He, Dan; Mao, Qiangdongzi; Jia, Jialin; Wang, Zhiyu; Liu, Yu; Liu, Tingting; Luo, Bangwei; Zhang, Zhiren (Frontiers in Immunology, 2022)
The efficient clearance of apoptotic cells (ACs), a process known as efferocytosis, is critical for immune homeostasis. While recent work has established an important interplay between efferocytosis and cellular metabolic changing, underlying mechanisms remain poor known. Here we discovered that pentose phosphate pathway (PPP) regulates tolerogenic ACs clearance and immune tolerance. ACs decreased expression levels of PPP-related genes and metabolites in macrophages. AG1, the agonist of PPP, increased the activity of PPP but greatly reduced macrophage phagocytosis of ACs and enhanced the inflammatory response of macrophage during efferocytosis. miR-323-5p regulated the expression of PPP-related genes and its levels increase during efferocytosis. miR-323-5p inhibitor greatly increased the expression level of PPP-related genes, reduced the macrophage phagocytosis of ACs and increased inflammatory response during efferocytosis, suggesting that miR-323-5p was essential in regulating PPP activity and AC clearance in macrophages. Correspondingly, the PPP agonist AG1 exacerbated the lupus-like symptoms in AC-induced systemic lupus erythematosus (SLE) model. Our study reveal that macrophage PPP is critical for tolerogenic ACs phagocytosis and interfering the PPP regulates the development of SLE in vivo, suggesting that regulating PPP–dependent metabolic reprogramming has potential therapeutic implications to harness immune-silent dying cell clearance and immune tolerance.